Sekitar tentang Penggunaan Laboratorium Bahasa - Sudja’i, M., Drs. (citeus, 1981)
This article explores the use of language laboratories as an educational technology tool that plays a crucial role in language teaching. Although language laboratories are often regarded as valuable facilities, in practice their pedagogical and technical implications are frequently overlooked after installation. Common issues include a lack of trained technicians, poor equipment maintenance, and the mismatch between laboratory usage and the actual goals of language learning. As a result, many laboratories fail to function optimally and eventually fall into disuse. This paper aims to outline the background, development, and future prospects of language laboratory utilization. It also emphasizes the importance of a comprehensive understanding of the laboratory’s function in order to maximize its effectiveness in supporting language education.